NILAI MORAL DALAM KUMPULAN CERPEN BH KARYA EMHA AINUN NADJIB - Rusi, Cita; Syam, Christanto; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the desire of researcher to find the moral values in a collection ofÂ BHÂ short stories by Emha Ainun Nadjib which is divided into four problems, namely the moral value reflected from human relation with God, human being with other human being, human being with themselves, and plan for the implementation in Indonesian language learning at school. This research aims to obtain an overview of moral values in a collection of BH short stories by Emha Ainun Nadjib. The researcher used descriptive method as a problem-solving step, namely describing moral values in a collection of BH short stories by Emha Ainun Nadjib. Based on the result of data research on a collection of BH short storiesÂ by Emha Ainun Nadjib, it can be concluded that there is a moral value that is reflected from human relation with God, the manifestation of it moral values are to pray to God, fear God, believe in God's destiny, be sincere, and grateful. The moral values reflected from human relation with other human being, the manifestation of their moral values are caring, tolerance, loyalty, justice, compassion and respect for the parent. The moral depicted from the human relationship with themselves, the manifestation of their moral values are responsibility, awareness, honesty, dedication, forgiveness, hard work, independence, patience, and courage.Keywords: the moral values, the collection of short stories, BH